Losing control : the emerging threats to western prosperity - King, Stephen D., 1963- (Yale University Press, 2010)
Argues that the future will bring major redistribution of wealth and power around the world, which will result in social and political consequences in the United States and Europe, when the population that is accustomed to living in prosperity must stop living beyond their means.